Cytology as a diagnostic aid - Matute Turizo, Gustavo; Jaramillo Vásquez, Martha Luz (Medicina UPB, 1997)
The papsmear as a diagnostic tool has been winning space in the medical practice and has been incorporated as a screening test for the diagnosis of cervical cancer. The authors wish to familiarize the doctor with the most important steps in the taking of the simple and preparation for its transfer ro the pathology laboratory where its processing and studies are done. A request for the study of a papsmear is an interconsultation that should comply with some minimum conditions and be accompanied by an adequate summary of the clinical history. The physician who requests the patient's papsmear should be familiarized with the interpretation of the results, as well as its reaches and limitations.
Keywords: Papsmear; Fixative; Papsmear study request; Bethesda system